A review of cyber vigilance tasks for network defense - Guidetti, Oliver Alfred; Speelman, Craig; Bouhlas, Peter (Frontiers in Neuroergonomics, 2023)
Vigilance decrement refers to a psychophysiological decline in the capacity to sustain attention to monotonous tasks after prolonged periods. A plethora of experimental tasks exist for researchers to study vigilance decrement in classic domains such as driving and air traffic control and baggage security, however the only cyber vigilance tasks reported in the research literature exist in the possession of the United States Air Force (Mancuso et al., 2015; McIntire et al., 2013; Sawyer et al., 2016). This review explores limitations in existent cyber vigilance tasks in the network defence space which do not accurately simulate the cognitive load associated with real world network defence command and control software. This review also identifies four essential challenges that must be overcome in the development of a modern, validated cyber vigilance task.